UNIFIED HANDHELD WITH SPECIAL SECURITY FOR PERVASIVE COMPUTING - Arya Kadyanan, I Gusti Agung Gede (Jurnal Ilmu Komputer; Vol 4 No 1: April 2011, 2011)
Abstract-Inspired by a swiss knife army with several other equipment that accompany such as pliers, screwdrivers, a corkscrew and many others. So as these devices are able to do everything. From this vision of the function of a handheld / smart-device which is growing rapidly and most people have today. How could a handheld perform all these functions? In this article will discuss about how to maximize handheld functions but still watched from the side of security. In short it’s how to ensure that all devices can be connected but still within our control
Keywords: pervasive computing, handheld, security, encryption ,Rijndael ,AES